Cutaneous manifestations of COVID‐19 among healthcare workers: A Case report and literature review. Issue 3 (16th March 2022) - Imen, Youssfi; Mechergui, Najla; Litaiem, Noureddine; Youssef, Imen; Gara, Soumaya; Zeglaoui, Faten; Rammeh, Soumaya; Ladhari, Nizar
Abstract: Common clinical features of COVID‐19 are increasingly known but cutaneous manifestations are rarely described among healthcare workers. A review of cutaneous manifestations of COVID‐19 especially among healthcare workers (HCW) is thus required. The aim of our current study was to provide a comprehensive review of cutaneous manifestations of COVID‐19 among HCW through six case reports and a literature review. We conducted a literature search for cases reports, original and review articles using PubMed and the Google search engines. We included the written English studies that mentioned cutaneous symptoms during COVID‐19 infection. In addition to the review, 6 cases were collected among the HCW working at the Charles Nicolle Hospital of Tunis from September 2020 to January 2021. In our review, we included 17 articles in addition to our six cases. The type of papers was case series and case reports in respectively 8 and 9 studies. Skin manifestations were reported in two studies including two HCW, in addition to our series of six HCW. Skin manifestations were chilblain‐like lesions (44.5%), a generalized macular or maculopapular exanthem (32.1%), a papulovesicular rash and chicken pox‐like vesicles (11.5%), painful acral red–purple papules (4.6%), urticaria (2.8%), purpuric or petechial lesions (2.3%), and livedo reticularis lesions (0.45%). Of the 218 cases, 203 cases have reported the location of lesions. The very great majority of lesions were found on the trunk, hands, and feet. Fifty‐one patients (23.4%) experienced lesions on the trunk. The time of onset of cutaneous lesions was variable. At the diagnosis or the onset of COVID‐19 symptoms, 8.3% (18/218) of patients presented with cutaneous lesions. After the onset of respiratory symptoms or COVID‐19 diagnosis, 36.7% (80/218) of patients presented with cutaneous lesions. Of the 197 cases with reported healing times, healing times were up to 24 days. COVID‐19 has been associated with different cutaneous manifestations, likely of varying pathophysiology and severity, some preceding COVID‐19 symptomatology and others occurring during active disease or later in the course. Thus, heightened awareness and timely recognition of cutaneous manifestations in COVID‐19 are important for occupational physicians treating HCW with COVID‐19. Abstract : COVID‐19 has been associated with different cutaneous manifestations, likely of varying pathophysiology and severity, some preceding COVID‐19 symptomatology and others occurring during active disease or later in the course. Thus, heightened awareness and timely recognition of cutaneous manifestations in COVID‐19 are important for occupational physicians treating HCW with COVID‐19